PATHOGENICITY OFCITRUS NEMATODE (TYLENCHULUS SEMIPENETRANS) ON CITRUS JAMBHIRI - U. Irshad; T. Mukhtar; M. Ashfaq; M. Z. Kayani; S. B. Kayani; M. Hanif; S. Aslam (Journal of Animal and Plant Sciences, 2012)
Citrus nematode (Tylenchulus semipenetrans) causes severe damage to citrus. In the present study the relationship between different initial densities of T. semipenetrans and reduction in growth parameters of Citrus jambhiri and nematode infestations was examined in pot experiment under greenhouse conditions using completely randomized design.  Seedlings of C. jambhiri were inoculated with T. semipenetrans at the rate of 0, 1,000, 2,000, 4,000 and 8,000 second stage juveniles/pot in the greenhouse. Data were collected on fresh and dry weights of the shoot and root, shoot length, nematode populations in the roots and soil and reproduction factor. All the data were subjected to analysis of variance and means were compared by Duncan’s Multiple Range Test at 5%. The relationships between number of galls and growth variables and nematode infestations were determined using regression analysis. It was observed that all the inoculum densities caused reductions in growth parameters and were found directly proportional to the inoculum density. Similarly, a direct relationship was observed between root and soil populations of the nematode and inoculum levels. On the other hand, the nematode build up was the maximum at lower inoculum level and an inverse relationship was observed between reproduction factor and inoculum densities of the nematode.
Keywords: Tylenchulus semipenetrans; citrus nematode; inoculum densities; rough lemon.